Differentiation of Mesenchymal Stem Cells Into Cardiac-like Cells by Co-induction of Lentiviruses Containing Mir-1 and Myocd in Chitosan Collagen Hydrogel Scaffold - Samaneh Khazaei (Qom University of Medical Sciences, 2021)
Background and Objectives: Cardiovascular disease is one of the leading causes of death worldwide. Mesenchymal stem cells (MSCs) are one of the most common sources of cell-based therapies in heart regeneration. There are several approaches to differentiate MSCs into cardiac-like cells, such as genetic modification. In addition, using of 3D culture, such as hydrogels, increases the efficiency of differentiation. Methods: In the present study, lentiviruses containing microRNA 1 (miR- 1) and myocardium (Myocd) were co-transducted to mouse adipose-derived MSCs. Three days after, transduced MSCs were transferred to a hydrogel containing chitosan and collagen. After 21 days, the differentiation of encapsulated cells was evaluated. In this regard, the expression of cardiac markers such as NK2 homeobox 5 (Nkx2-5), GATA binding protein 4 (Gata4) and troponin T type 2 (Tnnt2) at the level of gene and protein were investigated. Results: The results of real-time quantitative polymerase chain reaction (qRT-PCR) and immunocytochemistry showed that co-induction of miR-1 and Myocd in MSCs followed by transfer to composite hydrogel increased the expression of cardiac markers. Conclusion: The use of 3D culture such as chitosan/collagen hydrogel improves the differentiation of MSCs and subsequently obtains more mature cells for use in cell-based regenerative medicine